Legal Protection of Taka Bonerate Coral Reefs: Community Empowerment Perspective - Hasan, Yulia; Muhammmad Rusli; Baso Madiong; Andi Rijal Bangsawan (International Journal of Law Analytics, 2024)
Takabonerate is one of the national parks and the third-largest atoll area in the world. The Indonesian government has designated Selayar Regency, South Sulawesi, as a tourist destination because of its charming underwater panorama, which attracts foreign tourists to visit and see hundreds of species of fish and other natural resources. The aim of this research is to analyze the protection of the Takabonerate Coral Reef through community empowerment. This study uses a qualitative approach that refers to legal norms. The study results show that several international agreements regulating the importance of communities being involved in coral reef management have been ratified by the Indonesian Government and have been implemented in several laws and regulations